Terminology subset for the International Classification of Nursing Practice in Diabetes Mellitus - Fernanda Azeredo Chaves; Heloisa de Carvalho Torres; Tânia Couto Machado Chianca (Universidade de São Paulo, 2024)
Objective: to describe the process of developing a terminological subset for the International Classification of Nursing Practice in Diabetes Mellitus, based on Horta's Basic Human Needs Theory and Bandura's Social Cognitive Theory. Method: a methodological study based on the identification in the literature of 313 statements of nursing diagnoses pertinent to diabetes care, selected and validated by a consensus of nurses from different states of Brazil, specialists in diabetes, using the nominal group technique. Results: 156 nursing diagnosis/result statements were selected, of which 111 (71.15%) related to psychobiological needs, 42 (26.92%) to psychosocial needs and three (1.92%) to psychospiritual needs. A total of 433 nursing interventions were developed. The diagnostic statements were validated on the basis of a consensus among the experts, with an average content validity index of 0.89: 0.87 for psychobiological needs, 0.93 for psychosocial needs, and 0.77 for psychospiritual needs. Conclusion: the study validated the terminological subset for the International Classification of Nursing Practice in Diabetes, favoring clinical reasoning, the qualification of the Nursing Process, and the improvement of self-care practices in diabetes. It has made it possible to use nursing's own language based on a globally recognized classification.